Analisis Efektifitas Kinerja Mesin Cutting Manual Dan Otomatis Menggunakan Metode OEE (Overall Equipment Effectiveness ) Di PT. XYZ - Nur Hidayatul Ummah; Said Salim Dahda (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
Competition in the manufacturing industry is currently getting tougher due to rapid developments from time to time. The use of tools or machines as a supporting factor for the operation is something that cannot be separated in the industrial world. Therefore, engine performance is a factor that must be considered. Over time, machine performance will decline due to age, maintenance and minimal experience of human resources. In improving performance (effectiveness) to obtain productivity, researchers can calculate the level of performance effectiveness of manual and automatic (CNC) cutting machines. By measuring using the OEE (Overall Equipment Effectiveness) method. The steps in measuring the OEE method are carried out by taking into account Availability (A), Performance Efficiency (P) and Product Quality (R). Based on the advantages of OEE, further analysis of the calculation of Six big losses is carried out. Where the Overall Equipment Effectiveness (OEE) value of the Cutting Automatice (CNC) machine is 73.24% while the manual cutting machine is 55.32%. Both machines have not met the ideal OEE performance value of 85%. While the results of the calculation of Six big losses obtained a large value and affect the effectiveness of the two machines to be minimized is the Breakdown loss factor, Setup and Adjustment Loss and Defect Loss Process. So that continuous and periodic improvements are needed to maintain the effectiveness of both machines and increase productivity.